A Significant Regulatory Mutation Burden at a High‐Affinity Position of the CTCF Motif in Gastrointestinal Cancers. Issue 9 (2nd June 2016) - Umer, Husen M.; Cavalli, Marco; Dabrowski, Michal J.; Diamanti, Klev; Kruczyk, Marcin; Pan, Gang; Komorowski, Jan; Wadelius, Claes
Abstract : Regulatory mutations located at transcription factor motifs have impacts on gene regulation in cancer. We have detected motif‐breaking mutations with regulatory roles by combining genomic regulatory information with somatic mutations derived from whole genome sequencing of cancer and matching normal samples. We have found a striking mutation burden in the CTCF motifs in hepatocellular, gastric, pancreatic and esophagus cancers. For the first time, we have shown that genes located within topologically associated domains (TADs) are differentially expressed in the presence of CTCF mutations. Our results show functional characteristics of regulatory mutations in cancer ABSTRACT: Somatic mutations drive cancer and there are established ways to study those in coding sequences. It has been shown that some regulatory mutations are over‐represented in cancer. We develop a new strategy to find putative regulatory mutations based on experimentally established motifs for transcription factors (TFs). In total, we find 1, 552 candidate regulatory mutations predicted to significantly reduce binding affinity of many TFs in hepatocellular carcinoma and affecting binding of CTCF also in esophagus, gastric, and pancreatic cancers. Near mutated motifs, there is a significant enrichment of (1) genes mutated in cancer, (2) tumor‐suppressor genes, (3) genes in KEGG cancer pathways, and (4) sets of genes previously associated to cancer. Experimental and functional validations support the findings. The strategy can be applied to identify regulatory mutations in any cell type with established TF motifs and will aid identifications of genes contributing to cancer.